Pancreatic duct biopsies using a novel device delivery system for preoperative evaluation of main duct intraductal papillary mucinous neoplasm. Issue 4 (23rd March 2022) - Yokode, Masataka; Matsumori, Tomoaki; Uza, Norimitsu
Abstract : Watch a video of this article